(untitled) (Proceedings of Southern Federal University. Philology, 2021)
Ekaterina O. Kotova (Moscow, Russian Federation) The study is devoted to the use of a mathematical model for calculating the readability index of a text as one of the tools for linguoecological assessment of a journalistic text. The research material was 20 longreads published in Russian electronic editions. The specificity of the research object lies in the fact that it is both a kind of journalistic discourse and an element of the digital space. In the study formal mathematical and statistical research methods were used, based on the determination of readability values, i.e. ease of human perception of texts. A linguoecological assessment of Russian-language longreads was carried out on the basis of the universal readability indices, adapted to the Russian language, – the Flesch and the Flesch-Kincaid indices. The results obtained showed that longreads designed for a wide mass readership have a readability index ranging from “medium” to “very high”. Texts in which oral speech is actively transmitted have a high readability index. The author of the article concludes that this method should be used in the initial assessment of a journalistic text at the stage of editing the material, as well as in the framework of the linguoecological examination of significant publications. The study of the statistical parameters of journalistic materials made in this genre will help not only to assess the linguoecological situation in the space of modern virtual media, but also to include the results obtained in the overall picture of the analysis of the linguoecological situation in the Russian-speaking virtual space. Key words: linguoecology, longread, readability, Flesch index, FleschKincaid index, linguoecological analysis, linguoecological examination. DOI 10.18522/1995-0640-2021-2-67-76